Konstruksi Opini Publik Terhadap Pemberitaan Covid-19 Di Amerika Serikat - Andarini, Nuzlita; Rustanta, Agustinus (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research is done with the purpose of analyzing the framing used by Fox News and CNN to frame the issue of the U.S. President, Donald Trump’s, interview with politics journalist, Bob Woodward, for his new book, “Rage, which discusses the president’s downplay on the COVID-19 pandemic. The theory used in this research are Agenda Setting theory from Maxwell McCombs-Donald Shaw, and Propaganda theory from Harold Lasswell. This research will also use the study of hermeneutics as its research model. To collect data, Robert N. Entman’s framing analysis modelwill be used. As for the result of this research, it is discovered that FoxNewsdan CNNeach uses a different set off raming to frame President Donald Trump regarding news about COVID-19 in the United States. The frame used is especially heavier on news broadcasting of the downplay issue found in the Bob Woodward interview tapes. Fox News tend to defend President Donald Trump’s act of downplay, in order to protect his image. The media also constantly credits the president’s success on handling the COVID-19 pandemic. CNN on the other hand, is keen to expose the president’s carelessness and negligence in handling the pandemic, by bringing to light the false statements he made in the interview with Bob Woodward.